2015
DOI: 10.7554/elife.03913
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of sRNA quantitative variation analyzed using an experimental population derived from an elite rice hybrid

Abstract: We performed a genetic analysis of sRNA abundance in flag leaf from an immortalized F2 (IMF2) population in rice. We identified 53,613,739 unique sRNAs and 165,797 sRNA expression traits (s-traits). A total of 66,649 s-traits mapped 40,049 local-sQTLs and 30,809 distant-sQTLs. By defining 80,362 sRNA clusters, 22,263 sRNA cluster QTLs (scQTLs) were recovered for 20,249 of all the 50,139 sRNA cluster expression traits (sc-traits). The expression levels for most of s-traits from the same genes or the same sRNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 57 publications
5
23
0
Order By: Relevance
“…For RNA sequencing, ZS97, MH63, and the hybrid were grown in a phytotron with the day/night cycle set at 14 h/10 h and a temperature of 32°C/28°C. Tissues of seedling shoot at the four-leaf stage, developing panicle at stage III, and flag leaf at heading were collected for RNA sequencing following the procedures and protocols described previously (61).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For RNA sequencing, ZS97, MH63, and the hybrid were grown in a phytotron with the day/night cycle set at 14 h/10 h and a temperature of 32°C/28°C. Tissues of seedling shoot at the four-leaf stage, developing panicle at stage III, and flag leaf at heading were collected for RNA sequencing following the procedures and protocols described previously (61).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study showed that constructing individualized diploid genomes and transcriptomes by merging the parental genomes and transcriptomes for the hybrid improved the accuracy of quantification of gene expression levels compared with alignments to a single reference genome (61). This approach used RSEM (63), which has claimed to be capable of fully handling reads that map ambiguously between both isoforms and genes, to measure…”
Section: Methodsmentioning
confidence: 99%
“…They found a large number of cis-and trans-eQTLs that regulate the expression of genes, leading to the construction of the regulatory network through gene coexpression analysis (Wang et al, 2014c). Further analysis of the flag leaves of 98 immortalized F2 (IMF2) identified many genomic loci that control the expression abundance of small RNAs (Wang et al, 2015a), providing new insight into the regulation of gene expression.…”
Section: Gene Expression Profilesmentioning
confidence: 99%
“…Small RNAs were identified and quantified as described by Wang et al 63 with slight modifications. After filtering out low-quality reads and eliminating those matching tRNAs, rRNAs, snRNAs, and snoRNAs, the retained clean reads from 26 tissues or stages that were 18-26 nt in size were mapped to the maize AGPv4 reference genome using Bowtie-1.1.2 with the parameters unique location and no mismatch 51,61,64,65 .…”
Section: Srna Identification and Quantificationmentioning
confidence: 99%